Sustainable design: rattan for office green furniture / Muhammad Muizzuddin Darus - Darus, Muhammad Muizzuddin (2013)
This report writing explains and discusses the environmental issues about sustainable design. The researcher focuses on the sustainable material which is Rattan. Rattan is a very good material mainly because it is lightweight, durable and to a certain extent flexible which can be shaped into any free form compared to other sustainable materials. The keywords of this topic divided into four which are Sustainable design, Rattan, Rattan Furniture Design and Office Green Environment. The researcher will explain in depth these four keywords in this report writing. The main problem and issue regarding this topic is Malaysian rattan furniture craft tends to be bulky which waste materials to make certain product or craft. This problem will effect and create problem of the availability of the raw materials. So, the purpose of this study is to design functional form of rattan for Office Green Furniture without wasting rattan raw materials and the same time maintain our traditional identity in line with the modern furniture design.